Rethinking Epistemology: Narratives in Economics as a Social Science - JACKSON, Emerson Abraham (Theoretical and Practical Research in Economic Fields, 2023)
This research explores the incorporation of narrative perspectives in economics as a social science and its implications for rethinking epistemology. By examining the role of narratives in economic analysis, the study highlights the advantages of narratives in providing contextualized accounts of human experiences, connecting economic concepts to real-world phenomena, and exploring diverse perspectives. It emphasizes the importance of interdisciplinary collaboration between philosophers, economists, and social scientists to gain a comprehensive understanding of narratives' influence on economic decision-making, market dynamics, and consumer behavior. The research suggests that narratives offer a means to challenge the notion of a single, objective truth and contribute to a more inclusive and robust framework for analyzing economic phenomena. The implications extend beyond economics, urging a broader perspective on epistemology by embracing narrative perspectives and engaging in interdisciplinary collaboration across disciplines. Overall, this research calls for a rethinking of epistemology, recognising the significance of narratives and their role in knowledge production.